Comparative analysis of the activities of the largest Russian banking ecosystems - K. R. Alieva (Вестник Северо-Кавказского федерального университета)
Introduction. One of the main strategic trends today is the creation of ecosystems and innovative business models. Companies operating within the ecosystem become interesting objects for research in the economy. In this regard, special attention is paid to the comparison of modern ecosystems operating in the financial market of the Russian Federation, which include – Sber, VTB, Tinkoff.Goal. The study analyzes the conditions and features of modern trends in the banking sector regarding the formation of ecosystems.Materials and methods. The research is based on the analysis of literature sources using general scientific systematic and comparative methods, induction and deduction, and graphical representation of data.Results and discussion. The main result of the conducted research is to obtain specific conclusions about the activities of the largest representatives of banks in the Russian market regarding the formation of modern digital products, as well as the formation of the author’s definition of the concept of “banking ecosystem”.Conclusion. As a result of the study, the author determined that the banking ecosystem as a new digital product has a high degree of further development and transformation. This line of activity provides an opportunity for credit institutions to expand the scope of their activities, attract new potential customers, as well as increase the loyalty of consumers of services. If we talk about the general trend of the market, there is a steady trend of transition of Russian banks to a platform model of development.